PENGELOLAAN USAHA DAN STRATEGI PEMASARAN DALAM MENINGKATKAN MINAT KONSUMEN - iliza, Ika Nur; Febriana, Indah Ayu; Gunawan , Slamet; Alfaza, Muhammad Khafidz; Rahmawati, Ferida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Business management and marketing strategies play an important role in increasing consumer interest amid increasingly competitive business competition. This study aims to examine the concepts and principles of business management, marketing strategies in the business world, factors that influence consumer interest, as well as challenges and solutions in business management and marketing. The research method used is a qualitative descriptive approach by utilizing various relevant literature sources. The results of the study indicate that effective business management must be supported by proper planning, organizing, implementation, and supervision principles so that the business can operate optimally. In addition, marketing strategies such as promotion, product innovation, the use of digital media, and improving service quality have proven effective in attracting consumer interest in products and services offered. Consumer interest is influenced by several factors, including product quality, price, service, consumer needs, and the development of technology and social media. In practice, business owners face various challenges, such as market competition, changes in consumer behavior, limited capital, and lack of digital marketing skills. Therefore, solutions are needed in the form of business innovation, improving the quality of human resources, utilizing digital technology, and implementing creative and adaptive marketing strategies so that businesses can survive and continue to grow. With proper business management and marketing strategies, consumer interest can increase and provide a positive impact on business sustainability and development.